1965
DOI: 10.1139/z65-026
|View full text |Cite
|
Sign up to set email alerts
|

Prey Capture by Dragonfly Larvae (Odonata; Anisoptera)

Abstract: Dragonfly larvae catch prey by rapid protraction of a curiously modified labium. There are two main types of predatory behavior; 'climbers' move amongst aquatic vegetation and use their large compound eyes to detect prey at a distance and subsequently to orient towards it, while 'sprawlers' live at the bottom and detect most of their prey by tactile stimulation. Five species of dragonfly larvae were successful in 60 to 70% of their attacks on mosquito larvae, but in only 25 to 28% on gammarids. Size and moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
5

Year Published

1977
1977
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 3 publications
7
125
0
5
Order By: Relevance
“…The red and black in the tail of induced H. chrysoscelis could serve as defensive coloration or camouflage (Cott 1940;Endler 1978). Pritchard (1965) found that larval Aeshna dragonflies are attracted by, and strike at, erratically moving dummies within the size range of Hyla tail spots. In a field study, Acris tadpoles having black-tipped tails showed more predator-inflicted tail damage than tadpoles with plain tails (Caldwell 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The red and black in the tail of induced H. chrysoscelis could serve as defensive coloration or camouflage (Cott 1940;Endler 1978). Pritchard (1965) found that larval Aeshna dragonflies are attracted by, and strike at, erratically moving dummies within the size range of Hyla tail spots. In a field study, Acris tadpoles having black-tipped tails showed more predator-inflicted tail damage than tadpoles with plain tails (Caldwell 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Prey detection by aquatic predators is predominately tactile and visual; use of olfactory cues as main signals is uncommon and apparently absent in many metazoans (Greene, 1983;Peckarsky, 1984) but common in protists (Montagnes et al, 2008). Concurrent use of mechanical and visual stimuli is, however, common and their relative importance can change during ontogeny (Pritchard, 1965).…”
Section: Predator Foraging Traitsmentioning
confidence: 99%
“…Sit-and-wait predators and stalkers forage on moving prey; this behaviour is often linked to further behavioural or morphological adaptation enabling a fast strike (e.g., rapid protraction of the modified labium in dragonfly larvae: Pritchard, 1965). Active predators can be further classified by the geometry of movement (Čech and Kubečka, 2002;Jakobsen et al, 2005), which may have significant impact on predation rates.…”
Section: Predator Foraging Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Odonate nymphs and dytiscid larvae are visual predators -dytiscids are good swimmers and divers, but mostly prefer to feed close to the substrate (Tate and Hershey, 2003), whereas odonates sit and wait on the substrate and devour any passing prey (Pritchard, 1964(Pritchard, , 1965Smith and Pritchard, 1968; review by Batzer and Wissinger, 1996). Results from prior laboratory feeding experiments and gut content analyses of the dominant toppredators in Vandorf Pond are described in Febria et al (2005) -from these experiments we knew that the dytiscid larvae and Sympetrum nymphs in Vandorf Pond feed on ostracods, cladocerans, chironomids, culicids, nematodes, oligochaetes, leeches, dytiscid larvae, odonates, mites, algae, detritus, fungi, and leaf-and plant material.…”
Section: Manipulationsmentioning
confidence: 99%